Wandlungsdynamiken transnationaler Familien unter Krisenbedingungen Biographische Perspektiven auf Familienfigurationen zwischen Spanien und Ecuador - Schramm, Christian (Verlag Barbara Budrich, 2023)
When family members migrate internationally, it usually means a deep change in the relationships they maintain with each other. The author examines this process in families organized across borders between Ecuador and Spain. In doing so, the effects of the recent economic crisis in the country of arrival are considered in the light of a process of familial change that has lasted several decades. The particular resilience of familial power relations is thereby evaluated as ambivalent.